2015
DOI: 10.1007/s12035-015-9383-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-132 Regulates Dendritic Spine Structure by Direct Targeting of Matrix Metalloproteinase 9 mRNA

Abstract: Mir-132 is a neuronal activity-regulated microRNA that controls the morphology of dendritic spines and neuronal transmission. Similar activities have recently been attributed to matrix metalloproteinase-9 (MMP-9), an extrasynaptic protease. In the present study, we provide evidence that miR-132 directly regulates MMP-9 mRNA in neurons to modulate synaptic plasticity. With the use of luciferase reporter system, we show that miR-132 binds to the 3’UTR of MMP-9 mRNA to regulate its expression in neurons. The over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 47 publications
(68 reference statements)
1
51
0
Order By: Relevance
“…The RNA co-immunoprecipitation with anti-FMRP antibody was performed as published before [40,43]. Briefly, 1.6 mg of total protein from freshly prepared synaptoneurosomes from hippocampi and a part of adjacent cerebral cortex of male P30-40 WT and Fmr1 KO mice were lysed in 1200 μl precipitation buffer (10 mM HEPES, pH 7.4, 200 mM NaCl, 30 mM EDTA, 0.5% Triton X-100) with protease inhibitor cocktail cOmplete (Roche, Indianapolis, IN) and 80 U/ml RiboLock RNase Inhibitor (Thermo Scientific).…”
Section: Rna Co-immunoprecipitation and Qrt-pcrmentioning
confidence: 99%
“…The RNA co-immunoprecipitation with anti-FMRP antibody was performed as published before [40,43]. Briefly, 1.6 mg of total protein from freshly prepared synaptoneurosomes from hippocampi and a part of adjacent cerebral cortex of male P30-40 WT and Fmr1 KO mice were lysed in 1200 μl precipitation buffer (10 mM HEPES, pH 7.4, 200 mM NaCl, 30 mM EDTA, 0.5% Triton X-100) with protease inhibitor cocktail cOmplete (Roche, Indianapolis, IN) and 80 U/ml RiboLock RNase Inhibitor (Thermo Scientific).…”
Section: Rna Co-immunoprecipitation and Qrt-pcrmentioning
confidence: 99%
“…An association has been found between MMP2 and MMP9 and the processes of tumor cell invasion and metastasis in multiple types of human cancer, including uterine neoplasms (39). Jasińska et al (40) reported that miR-132 regulated the structural plasticity of dendritic spines through directly repressing the expression of MMP9. In the present study, miR-132 significantly downregulated the expression of proliferation-associated proteins Ki-67 and PCNA, and invasion-associated enzymes MMP2 and MMP9 in CC cells, and further suppressed the proliferation and invasion of CC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…On the post-transcription level several pathways may activate the degradation of MMP-9 mRNAs [19]. Besides, regulations by microRNAs have been recently reported [20,21]. In neurons an additional level of MMP-9 regulation is its local translation in synapto-dendritic compartment.…”
Section: Mmp 9 Molculementioning
confidence: 99%